2006
DOI: 10.1037/0882-7974.21.4.826
|View full text |Cite
|
Sign up to set email alerts
|

Attentional disregulation: A benefit for implicit memory.

Abstract: We investigated the effect of age and time of testing on the ability to control attention, and addressed the possibility that older adults' susceptibility to distraction may sometimes facilitate performance on a later cognitive task. Using a modification of Rees et al. (1999), participants made same/different judgements on line-drawings superimposed with task-irrelevant letter strings. Memory for the distractors was subsequently tested using an implicit memory task. Both older and younger adults demonstrated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
163
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(192 citation statements)
references
References 40 publications
24
163
1
Order By: Relevance
“…We confirm previously established behavioral effects showing that at synchrony, older adults are able to resist distraction (Hasher et al, 2005;Rowe et al, 2006;Schmidt et al, 2007), and crucially for the first time, demonstrate that to do so they activate a set of attentional control regions recruited by younger adults. Older adults tested in the afternoon during their off-peak time of day showed both a behavioral and neural decrement, as they are not as able to resist distraction nor draw on the appropriate brain regions as their young peers or age mates tested in the morning.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We confirm previously established behavioral effects showing that at synchrony, older adults are able to resist distraction (Hasher et al, 2005;Rowe et al, 2006;Schmidt et al, 2007), and crucially for the first time, demonstrate that to do so they activate a set of attentional control regions recruited by younger adults. Older adults tested in the afternoon during their off-peak time of day showed both a behavioral and neural decrement, as they are not as able to resist distraction nor draw on the appropriate brain regions as their young peers or age mates tested in the morning.…”
Section: Discussionsupporting
confidence: 89%
“…The overall ANOVA was significant, F (2, 46) = 3.5, p = .038, the linear contrast was also significant, p = 0.017 and suggested that priming increased from nil in young adults to 7% in the morning group, and finally 11% in old adults tested in the afternoon. Our current results therefore agree with both the age and time of day differences reported previously Rowe et al, 2006).…”
Section: Cihr Author Manuscriptsupporting
confidence: 94%
See 1 more Smart Citation
“…Deficits in inhibitory processing allow too much information into memory, leading on some occasions to competition at retrieval between relevant and irrelevant information (Hasher & Zacks, 1988;May, Zacks, Hasher, & Multhaup, 1999). By contrast, should the irrelevant information become relevant, older adults can also show a performance advantage over young adults (Kim, Hasher, & Zacks, in press;Rowe, Valderrama, Hasher, & Lenartowicz, 2006). On the second account, agerelated declines in memory performance are due to a binding deficit at encoding that prevents information from being stored successfully into a memory representation that can later be retrieved (e.g., Chalfonte & Johnson, 1996).…”
mentioning
confidence: 99%
“…There is some evidence to suggest that having processed an irrelevant stimulus (for which there is an existing representation in memory) as a result of an inhibitory deficit confers an advantage in a subsequent priming task for older adults (Hasher et al, 1997;Kim et al, in press;Rowe et al, 2006). However, it remains unclear whether the additional information encoded by older adults can be bound into a memory representation with other processed information.…”
mentioning
confidence: 99%